LITERASI SEJARAH MELALUI KEGIATAN EKSTRAKURIKULER HISTORY CLUB DI SMA 48 JAKARTA - Kurniawati Kurniawati; Corry Iriani Rochalina; Ponco Setiyonugroho; Alfa Ardiansyah; maulani lani (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract History Club extracurricular activities can be a solution for learning history that is meaningful and attracts students' interest. The History Club is the right place to popularize history in schools because history learning has so far been less attractive to students as happened at SMA 48 Jakarta. Teachers need to hone creativity so that students are interested in learning history, one of which is through the History Club which can be used by teachers in exploring historical literacy such as the use of historical sources. However, the use of primary sources in history learning is not yet popular in Indonesia, so presenting historians is one solution as a method of activity. The result is that History Club activities can be a solution to popularize history in schools. Students enrich the historical material they get in class by asking historians who are accustomed to working with primary sources. It can be 2 concluded that studying history by presenting historical sources in schools can make history learning more meaningful for students. Abstrak Kegiatan ekstrakurikuler History Club dapat menjadi salah satu solusi pembelajaran sejarah yang bermakna dan menarik minat siswa. History Club merupakan sebagai wadah yang tepat untuk mempopulerkan sejarah di sekolah-sekolah karena pembelajaran sejarah selama ini kurang diminati oleh siswa sebagaimana yang terjadi di SMA 48 Jakarta. Guru perlu mengasah kreativitas agar siswa tertarik belajar sejarah salah satunya melalui History Club yang dapat digunakan guru dalam mengeksplorasi literasi sejarah seperti penggunaan sumber sejarah. Namun begitu penggunaan sumber primer dalam pembelajaran sejarah belum popular di Indonesia maka menghadirkan sejarawan menjadi salah satu solusi sebagai metode kegiatan. Hasilnya adalah kegiatan History Club dapat menjadi solusi untuk mempopulerkan sejarah di sekolah-sekolah. Siswa mendapat pengayaan materi sejarah yang didapatnya di kelas dengan bertanya langsung kepada sejarawan yang terbiasa bekerja dengan sumber primer. Dapat disimpulkan bahwa mempelajari sejarah dengan menghadirkan sumber sejarah di sekolah dapat menjadikan pembelajaran sejarah lebih bermakna bagi siswa.